Thalidomide Inhibits TGF-β1-induced Epithelial to Mesenchymal Transition in Alveolar Epithelial Cells via Smad-Dependent and Smad-Independent Signaling Pathways. Issue 1 (December 2017) - Zhou, Xian-Long; Xu, Peng; Chen, Hai-Hua; Zhao, Yan; Shen, Jun; Jiang, Cheng; Jiang, Shan; Ni, Shao-Zhou; Xu, Bing; Li, Lei
Abstract Recent evidence indicates that the epithelial to mesenchymal transition (EMT) in primary alveolar cells (AECs) plays an important role in idiopathic pulmonary fibrosis (IPF).In vivo models have suggested that thalidomide (THL) has anti-fibrotic effects against pulmonary fibrosis, but the underlying mechanism of this effect is not clear. This study investigated whether THL regulates alveolar EMT and the possible mechanisms underlying this process. CCL-149 cells were treated with TGF-β1 in the presence of THL at the indicated concentrations. EMT was assessed by changes in cell morphology and in phenotypic markers. Signaling pathways involved in EMT were characterized by western blot analysis. THL inhibited the TGF-β1 induction of α-SMA, vimentin, MMP-2/-9 and collagen type IV expression and restored the morphological changes in primary alveolar epithelial cells caused by TGF-β1. TGF-β1 induction of α-SMA expression was partially dependent on the activation of p38, JNK, ERK, Akt, Smad 2 and Smad3. Moreover, THL inhibited TGF-β1-induced phosphorylation of p38, JNK, ERK, Akt, GSK3β, Smad 2 and Smad3 without altering the total expression levels of those proteins. These findings indicate that TGF-β1-induced EMT in alveolar epithelial cells is inhibited by THL via both Smad-dependent and non-Smad-dependent signaling pathways and suggests therapeutic approaches for targeting this process in pulmonary fibrosis.